There is no more Haiti : between life and death in Port-au-Prince - Beckett, Greg, 1975- (Oakland, California : University of California Press, 2019)
"This is not a book about crisis in Haiti. This is a book about what it feels like to live, and sometimes to die, with crisis. It is about the experience of living with a crisis that seems to never end, to only turn into more crises, more disasters, more emergencies, and more interventions. How Crisis Feels also explores the power of stories to help us make sense of the world and to understand the experience of others. Greg Beckett draws on over a decade of research to trace how people navigate the ruins of ecological devastation, economic collapse, political upheaval, violence, and humanitarian disasters in Port-au-Prince, Haiti"--Provided by publisher.
Introduction -- The forest and the city -- Looking for life -- Making disorder -- Between life and death -- Aftermath -- Postscript.
Includes bibliographical references and index.
Keywords: Haiti -- Social conditions -- 21st century; Haiti -- History -- 1986-